Effectiveness Of Baby Massage At The Age Of 3 - 12 Months On The Quality Of Baby Sleep - Dewi Sapta Wati; Wahyu Utami Ekasari (Jurnal Profesi Bidan Indonesia, 2022)
Background: The quality of a baby's sleep is the quality of the physiological state that is obtained while the baby is sleeping, which restores the body's processes that occur when the baby wakes up with the right amount of sleep. Sleep plays a very big role for the development of the baby. However, about 25% of sleep disturbances occur in infants, thereby disrupting the quality of the baby's sleep. Purpose: to know the effectiveness of baby massage in helping babies to get good quality sleep in the process of baby's growth and development. Methods This research is a quantitative study using the pre-experimental design method with the on group pretest - posttest design. The sample in this study were infants aged 3-12 months who were immunized by Amalia Temon's TPMB. Sampling with purposive sampling technique obtained a total sample of 15 respondents. Methods of data analysis using non-parametric static analysis techniques Wilcoxon and Mann Whitney with α 0.05. Results: From the results of the study on 15 respondents, the results showed differences in the pretest and posttest in the intervention group, namely an increase in the quality of sleep for infants after treatment, namely a difference in the mean pretest 2.42 and the mean posttest 4.28 with the result P = 0.001 < α 0.05 .   Conclusion: From the results of research on 15 respondents, it was found that baby massage was effective in improving sleep quality in infants aged 3-12 months